2018
DOI: 10.1177/1708538118814611
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate product level as a predictor for arteriovenous fistula re-operations in patients with chronic renal failure

Abstract: Objectives There is an increased calcium phosphate product level causing the formation of calcification in the arterial wall and thus decreased quality of fistula in patients with chronic renal failure. The purpose of our study is to verify the relationship between arteriovenous fistula re-operation and high calcium phosphate product level. Methods Seventy-nine consecutive patients with chronic renal failure between April 2016 and February 2018 were included in the study. Patients having calcium phosphate prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Additionally, the high baseline level of total serum calcium acts as protective factor against vascular access maturation failure (OR:0.17, p = 0.002). Similar to our results, Tuysuz et al [ 60 ] demonstrated in a group of 79 patients that serum levels of phosphate (OR: 1.85, p = 0.05) and Ca-P product (OR: 1.11, p = 0.03) were predictive factors of AVF re-operation. Moreover, Unver et al [ 61 ] demonstrated that high values of Ca-P product are associated with lower blood flow rates ( p = 0.03).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the high baseline level of total serum calcium acts as protective factor against vascular access maturation failure (OR:0.17, p = 0.002). Similar to our results, Tuysuz et al [ 60 ] demonstrated in a group of 79 patients that serum levels of phosphate (OR: 1.85, p = 0.05) and Ca-P product (OR: 1.11, p = 0.03) were predictive factors of AVF re-operation. Moreover, Unver et al [ 61 ] demonstrated that high values of Ca-P product are associated with lower blood flow rates ( p = 0.03).…”
Section: Discussionsupporting
confidence: 92%
“…The serum levels of calcium, phosphate, and Ca-P product have an important role in the homeostasis and optimal functioning of the cardiovascular system [ 3 , 60 , 61 ]. According to the results of our study, the low level of serum calcium ( p = 0.0002), the increased level of serum phosphate ( p < 0.0001), and the increased values of Ca-P product ( p < 0.0001) are associated with AVF maturation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, female sex, obesity, diabetes mellitus, extensive vascular disease, surgeon's experience, and even increased calcium phosphate product levels have been thought as the main clinical and chemical predictors of establishment and maintenance of vascular access. [11][12][13][14][15] Effective access surveillance and maintenance programs should be based on routine physical and CDUS examination, and surgical/endovascular intervention modalities should be considered, if needed. Currently, the benefit of surgeon-based CDUS concept has become more apparent in vascular access surgery.…”
Section: Discussionmentioning
confidence: 99%